IMPROVING PRE-HOSPITAL PAEDIATRIC PAIN MANAGEMENT. Issue 6 (19th May 2015) - Shaw, Joanna; Fothergill, Rachael; Virdi, Gurkamal
Abstract : Introduction: Pain is one of the most frequently reported symptoms to UK ambulance services and pain management is a known area for improvement. This is especially true for paediatric patients who may not be able to communicate their levels of pain as effectively as adults. Method: A criterion-based retrospective clinical audit evaluated pain assessment and management for children less than 12 years old who reported a suspected fracture. To determine how pain assessments could be improved, an investigation of pain assessment methods used in other areas of the NHS was undertaken. A laminated card was produced and distributed to all clinicians for use when assessing pain in children. The card contains an amended version of the Wong-Baker faces to help clinicians assess and monitor paediatric patients' levels of pain with a reminder of the analgesic options available for children. Paediatric pain assessment and pain management was re-audited following introduction of the card. Results: Prior to introduction of the card, the data showed paediatric pain management as a considerable area of concern for the ambulance service. A pain assessment was undertaken for 64% of patients. When a pain assessment was undertaken, and the child reported they were in pain, only 23% of patients received pharmacological pain relief. The introduction of the card resulted in great improvements. A pain assessment was documented for 96% of patients, representing an improvement of 32% from the original audit. When analgesia was indicated, it was administered to 66% of patients, an improvement of 43%. Despite this improvement, pain was still not managed effectively for 34% of patients. Conclusion: Further improvement is required to ensure every paediatric patient has their pain assessed and managed effectively. The laminated card has been redesigned and distributed, in conjunction with a pain training strategy. In addition, further analgesic options for paediatric patients have been investigated.